Pengaruh desain produk dan harga terhadap minat beli konsumen mebel jati jepara pada Toko Usaha Baru Furniture di Lubuk Alung - Sutiyem, Sutiyem; Ravelby, Thesa Alif; Trismiyanti, Dessy (Jurnal Kajian Manajemen Bisnis, 2019)
This study aims to determine the effect of product design and price on consumer interest in buying Jepara Teak furniture at the New Furniture Business Shop in Lubuk Alung. This type of research is associative quantitative research, the number of research samples were 100 people. Data was collected in the form of questionnaires and using analyzed SPSS software ver.21.0 for Windows. The conclusions from this study is the product design variable (X1) has a significant positive effect on purchase decision in Jati Jepara furniture at the New Furniture Business Shop in Lubuk Alung, as evidenced by t value > t table (10,400> 1,660) and a significant influence between price variables ( X2) purchase decision with t value> t table (2,015> 1,660). There is a positive and significant influence between product design (X1) price (X2), on purchase decision of Jati Jepara furniture consumers with an F-value 156,644> F- table (3,09) means that it affects together. The coefficient of determination (RÂ²) results obtained a coefficient of 0.764 or 76.4%, while 23.6% is influenced by other variables.Keywords: Product design; prices; purchase decision.